Exploring Suitable Utilization of Waste Tires in Chiang Mai - Senghaphan S. (2017)
© 2017 The Authors. The study aims at utilizing waste tires in Chiang Mai municipal area. As there are approximately 27,000 waste tires per month, by which each contains up to 37 MJ/kg, there must be a better way than dumping. Therefore, the study explores the feasibilities of utilizing these waste tires by establishing (i) a rubber crumbing factory, (ii) a pyrolysis plant and (iii) a rubber power plant. Here, the site is firstly selected based on available supply, using basic optimization models. Then, the study focuses on the feasibility of demand, engineering, finance and social/ environment response of the three options. Finally, analytic hierarchy process is used to reflect the suitability of the options based on factors of interest. Within the options considered, a pyrolysis plant appears to be the most attractive.